Implementation of Covid-19 Prevention at SDN Sugiharjo II, Tuban Regency - Kusuma Dwi Nur M; Nurul Ngainin (Madrosatuna: Journal of Islamic Elementary School, 2021)
In Indonesia in 2019 in December, a disease caused by the Coronavirus SARS-COV-2, which is now better known as Covid-19, emerged. Covid-19 is a type of disease that attacks the respiratory tract and is very dangerous for human life. The level of knowledge about Covid-19 is still very little, even the public still does not understand correctly about Covid-9 so that awareness of the dangers of Covid-19 is very minimal. Meanwhile, the spread is always increasing. Covid-19 prevention must be done immediately. The IAINU Tuban tertiary institution also participates in the prevention of covid-19 transmission through one form of activity Against Covid-19 Prevention at SDN Sugiharjo II, Tuban Regency. The objectives of this research are: (1) Describing and Analyzing the Implementation Process of Prevention of Covid-19 at SDN Sugiharjo II, Tuban Regency, (2) Describing and Analyzing the Prevention of Covid-19 at SDN Sugiharjo II, Tuban Regency, and (3) Describing and Analyzing the impact of Implementation on Prevention of Covid-19 at SDN Sugiharjo II, Tuban Regency. This study uses qualitative research types of field research (field research). Data collection techniques by means of observation, interviews and documentation. Meanwhile, the data analysis technique uses descriptive qualitative, which describes or describes in detail the data found. The technique of checking the validity of the data used the data triangulation method, peer discussion, attendance extension, and informant reviews. The results of this study indicate that: (1) The Implementation Process of Covid-19 Prevention at SDN Sugiharjo II, Tuban Regency, which goes through two processes before its implementation: First, the process before going to the field, and secondly the process of field work (implementation of the implementation of prevention of Covid-19 at SDN Sugiharjo 2). (2) The role of preventing covid-19 at SDN Sugiharjo. (3) The impact of this activity is to add insight to the public about the importance of preventing Covid-19, the community is increasingly more aware of Covid-19, and the community applies 3M (wearing masks, washing hands, and maintaining distance).